2022
DOI: 10.1021/acs.inorgchem.2c00307
|View full text |Cite
|
Sign up to set email alerts
|

Organic Crystalline Solid Electrolytes with High Mg-Ion Conductivity Composed of Nonflammable Ionic Liquid Analogs and Mg(TFSA)2

Abstract: The development of solid electrolytes with Mg-ion conductivity at room temperature is an important issue to achieve all-solid magnesium batteries. We focus on organic ionic crystals with Mg-ion conduction paths in addition to nonflammable and nonvolatile features as an innovative candidate of solid electrolytes with Mg-ion conductivity. Herein, we show the development of novel organic ionic crystals, [N­(CH3)4–n (CH2CH3) n ]­[Mg­{N­(SO2CF3)2}3] (n = 0 or 2), using analogs of ionic liquids, [N­(CH3)4]­[N­(SO2CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In this context, tremendous research is ongoing to improve the ionic conductivities of oxides, [8][9][10][11][12] suldes, [13][14][15] hydrides, [16][17][18] metal-organic frameworks (MOFs), 19,20 and molecular crystals. [21][22][23] Among the various materials reported to date, complex hydrides have received considerable attention because of their high ionic conductivities, superior electrochemical stabilities, high deformabilities, and low material densities. 24,25 Complex hydrides are represented by the formula M ′ x (M ′ ′ y H z ), where M ′ represents a metal cation, such as Li + , Na + , Mg 2+ , or Zn 2+ , and M ′′ y H z represents complex anions such as [BH 4 ] − , [AlH 6 ] − , [B 12 H 12 ] 2− , [CB 11 H 12 ] − , or [CB 9 H 10 ] − .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, tremendous research is ongoing to improve the ionic conductivities of oxides, [8][9][10][11][12] suldes, [13][14][15] hydrides, [16][17][18] metal-organic frameworks (MOFs), 19,20 and molecular crystals. [21][22][23] Among the various materials reported to date, complex hydrides have received considerable attention because of their high ionic conductivities, superior electrochemical stabilities, high deformabilities, and low material densities. 24,25 Complex hydrides are represented by the formula M ′ x (M ′ ′ y H z ), where M ′ represents a metal cation, such as Li + , Na + , Mg 2+ , or Zn 2+ , and M ′′ y H z represents complex anions such as [BH 4 ] − , [AlH 6 ] − , [B 12 H 12 ] 2− , [CB 11 H 12 ] − , or [CB 9 H 10 ] − .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, tremendous research is ongoing to improve the ionic conductivities of oxides, 8–12 sulfides, 13–15 hydrides, 16–18 metal–organic frameworks (MOFs), 19,20 and molecular crystals. 21–23 Among the various materials reported to date, complex hydrides have received considerable attention because of their high ionic conductivities, superior electrochemical stabilities, high deformabilities, and low material densities. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…The paths are precisely controlled by organic molecules and Mg salts. Only two Mg ion conductive organic crystal electrolytes have been reported so far [154,155]. In both cases, their room temperature conductivities were higher or comparable to Mg(BH 4 ) 2 -based inorganic electrolytes, and the cation transference number was higher than that of polymer-based electrolytes.…”
Section: Organic Crystal Electrolytesmentioning
confidence: 94%
“…Unlike previous research that incorporates ILs into the pores of MOFs to facilitate their melting, our material design relies on the incorporation of the IL components into the CP framework to achieve meltability . One related study that has been recently reported is the preparation of CPs from fluorine-containing ILs and metal salts . As structurally related compounds, many anionic CPs containing onium cations have been reported, which are regarded as dense MOFs. , Among them, the melting and vitrification of [cation]­[M­(dicyanamide) 3 ] has been reported .…”
Section: Introductionmentioning
confidence: 99%